Important physico-chemical parameters and sediment characteristics of some selected sites in the Jaffna estuary - Sivashanthini, K.; Sutharshiny, S.; Gunaalan, K.; Tharmine, A.; Veronika, K.; Digamadulla, K.M.D.S. (University of Jaffna, 2016)
The present study was carried out to investigate the spatial variation of physico - chemical parameters and sediment characteristics in some areas of the Jaffna estuary in order to assess the differences among sites with respect to the measured parameters. A total of 29 stratified samplings were made on a fortnightly basis from October 2013 to April 2014. Surface water samples were collected along the selected GPS 12 Channel and physico-chemical parameters and bottom characteristics were also measured. Estuary depths increased significantly (p<0.05) from 40 to 770 cm at Nagathevanthurai, Pooneryn and Mandaitivu I respectively though water temperature was not significantly different. Salinity values were significantly (p<0.05) different with a wide range having 60 ppt at Chavakachcheri while it was 32 ppt in Mandaitivu IV. Water pH was alkaline at most of the sampling sites. Minimum value of electrical conductivity was recorded in Mandaitivu I as 15.56 mS/cm and the electrical conductivity value at Ketpali was 29.50 mS/ cm. The turbidity range was between 12.64 – 48.50 g/L with the lowest values at Velanai I (Allaipitty) and significantly (p<0.05) higher values were recorded at Kachchai. The dissolved oxygen concentration measured at Velanai III (Chettypullam) was significantly (p<0.05) high (12.47 mg/L) and the lowest value was recorded at Pooneryn II (Poovarasamtheevu), which was 7.00 mg/L. Percentage of organic matter in the Kakkaitheevu I (Madaaruku) and Mandaitivu I ranged between 1.04 and 6.80 respectively. Percentage of silt – mud was followed by sand were the prominent sediment features in the Jaffna estuary. Results of the present study emphasize the spatial heterogeneity of physico-chemical and bottom characteristics in the Jaffna estuary.
Keywords: Bottom characteristics; Jaffna estuary; Physico-chemical parameters